Efektivitas Pemberian Metode Pijat Oksitosin Dan Pijat Akupresur Terhadap Lama Persalinan Kala I Fase Aktif: The Effectiveness of Oxytocin Massage Methods and Acupressure Massage Methods for Active Phase I Labor Period - Yuliawati, Lia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: In Banten, in 2019 the cause of maternal death was recorded at 22,5% caused by other causes, one of which was due to prolonged labor, as well as Cimanggu Health Center in 2021 found 1 case of maternal death caused by bleeding the cause was due to prolonged parturition. One way to speed up the progress of labor is by giving oxytocin massage and acupressure massage. The purpose of the study was to determine the effectiveness of giving oxytocin massage and acupressure massage for the duration of the active phase of the first stage of labor at the Cimanggu Health Center, Pandeglang Regency, Banten in 2022.  Methods: The research method was a quasi-experimental design with a post-test-only design with control groups, the number of samples was 60 respondents, the sampling technique was purposive sampling, and data analysis using the Independent T-test.    Result: The results of the study showed that the duration of the first stage of active labor in the oxytocin massage group obtained an average of = 6,84 hours, the duration of the active phase of the first stage of labor in the acupressure massage group obtained an average of 5,34 hours. The results of the bivariate analysis showed that there was an average difference between oxytocin massage and acupressure massage on the duration of the active phase of the first stage of labor with a p-value of 0,000.  Discussion: The conclusion of the study was that there was an average difference between oxytocin massage and acupressure massage on the duration of the active phase of the first stage of labor. Suggestions are expected for health workers, are expected to always be updated, especially in helping mothers give birth to meet the mother's need for comfort in non-pharmacological pain control, one of which is using acupressure or oxytocin massage techniques.